1978
DOI: 10.1073/pnas.75.5.2135
|View full text |Cite
|
Sign up to set email alerts
|

Fluorescent labeling of hormone receptors in viable cells: preparation and properties of highly fluorescent derivatives of epidermal growth factor and insulin.

Abstract: Highly fluorescent analogs of insulin and e idermal growth factor were repared by the covalent attachment of these peptides to a--actalbumin molecules that were highly substituted (i.e., seven to one) with rhodamine molecules. The a-lactalbumin was specifically linked to the lysine residue of insulin or to the a-amino group of epidermal growth factor. The insulin derivative retained 1.15% of its potency in stimulating glucose oxidation in fat cells but retained about 8 Fluorescence microscopy is used extensive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
35
0

Year Published

1980
1980
1997
1997

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 122 publications
(35 citation statements)
references
References 19 publications
0
35
0
Order By: Relevance
“…were found for these mutants, whether or not they were cleaved with CNBr. Experiments on EGF and TGF-a have shown that an N-terminal extension does not markedly modify EGF-binding activity (12,26). Therefore, the loss of activity obtained with [Met-48]-TGF-a that has not been CNBr treated was probably due to the mutation itself and not to the N-terminally extended fusion protein.…”
Section: Resultsmentioning
confidence: 97%
“…were found for these mutants, whether or not they were cleaved with CNBr. Experiments on EGF and TGF-a have shown that an N-terminal extension does not markedly modify EGF-binding activity (12,26). Therefore, the loss of activity obtained with [Met-48]-TGF-a that has not been CNBr treated was probably due to the mutation itself and not to the N-terminally extended fusion protein.…”
Section: Resultsmentioning
confidence: 97%
“…In addition to being phosphorylated, insulin-occupied receptors move laterally within the plasma membrane and into clathrin-coated pits (25,31,(34)(35)(36)(37). Thus in the presence ofinsulin, there is a net flux ofoccupied receptors into coated pits, from which they enter the coated vesicle-endosome continuum.…”
Section: Discussionmentioning
confidence: 99%
“…Chlorin e 6 was initially reacted with 1,6-diaminohexane (Sigma) using CMCS (ratio of chlorin e 6 to 1,6-diaminohexane to CMCS of 1:100:100) in 10 mM sodium phosphate buffer, pH 7.0, and CMCS was subsequently used to link aminochlorin e 6 with the P10/␤-galactosidase carrier in the same buffer (ratio of carrier to aminochlorin e 6 to CMCS of 1:30:300). After successive reaction of insulin with citraconic anhydride (18) (Serva) and SPDP (ratio of 1:6) in 25 mM Hepes, 150 mM NaCl, pH 7.5 (buffer B), citraconic-insulin-PDP was linked to P10-chlorin e 6 or ␤-galactosidase-chlorin e 6 (ratio of 15:1) in buffer B, after which the citraconic groups were removed (18). Two series of constructs were made: P10-(chlorin e 6 )-insulin (1:5:7), ␤-galactosidase-(chlorin e 6 )-insulin (1:5: 7), and P10-(chlorin e 6 )-insulin (1:3:8) and ␤-galactosidase-(chlorin e 6 )-insulin (1:2:8).…”
Section: Methodsmentioning
confidence: 99%